High-throughput ultrasensitive molecular techniques for quantifying low-density malaria parasitemias. - Imwong, M; Hanchana, S; Malleret, B; Rénia, L; Day, N; Dondorp, A; Nosten, F; Snounou, G; White, N (American Society for Microbiology, 2014)
The epidemiology of malaria in "low-transmission" areas has been underestimated. Molecular detection methods have revealed higher prevalences of malaria than conventional microscopy or rapid diagnostic tests, but these typically evaluate finger-prick capillary blood samples (∼5 μl) and therefore cannot detect parasite densities of <200/ml. Their use underestimates true parasite carriage rates. To characterize the epidemiology of malaria in low-transmission settings and plan elimination strategies, more sensitive quantitative PCR (qPCR) is needed to identify and quantify low-density malaria parasitemias. A highly sensitive "high-volume" quantitative PCR (qPCR) method based on Plasmodium sp. 18S RNA was adapted for blood sample volumes of ≥250 μl and scaled for high throughput. The methods were validated by assessment of the analytical sensitivity and specificity, diagnostic sensitivity, and specificity, efficiency, precision, analytical and diagnostic accuracies, limit of detection, root cause analysis of false positives, and robustness. The high-volume qPCR method based on Plasmodium sp. 18S RNA gave high PCR efficiency of 90 to 105%. Concentrations of parasite DNA from large volumes of blood gave a consistent analytical detection limit (LOD) of 22 parasites/ml (95% CI, 21.79 to 74.9), which is some 2,500 times more sensitive than conventional microscopy and 50 times more sensitive than currently used PCR methods from filter paper blood spots. The diagnostic specificity was 99.75%. Using automated procedures it was possible to process 700 blood samples per week. A very sensitive and specific high-throughput high-volume qPCR method for the detection of low-density parasitemias (>20 parasites/ml) was developed and validated.